(untitled) (Bangladesh Journal of Medical Science, 2013)
A 64 years male farmer presented with history of painless gross hematuria for 1 month and severe loss of weight and appetite for 2 months. There was a history of single episode of fever for 1 day without chills and rigors, about 1 month ago. There was no history of tuberculosis. On examination patient had severe pallor, no raised temperature and no tenderness at renal angle. His hemoglobin on admission was 5.7gm%. Enhanced CT scan showed right kidney having irregular low density lesion at the lower pole with perirenal fluid collection. Urine for culture sensitivity showed growth of Escherichia coli sensitive to norfloxacin and so patient was put on oral norfloxacin for 14 days. A CT guided fine needle aspiration biopsy was planned for the patient for a definite diagnosis. But a repeat ultasonography before the procedure, showed both kidneys to be normal. The lesion had vanished! Bangladesh Journal of Medical Science Vol. 12 No. 03 July 13 Page 339-340 DOI: http://dx.doi.org/10.3329/bjms.v12i3.11793